The Effect Of Liquidity Ratio And Solvency On Profitability In Pt Agung Podomoro Land Tbk Period 2015-2019 - Elisa Christin Hagai Tarigan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2022)
The purpose of this study is to prove whether there is an effect of liquidity and solvency on profitability at PT Agung Podomoro Land Tbk. The data collection method used is the method of literature and field research, then the data is analyzed using the multiple linear regression analysis method with the help of SPSS software version 22. The results of the study state that liquidity is proxied by the current ratio and solvency is proxied by debt to assets ratio both in terms of partial or simultaneous have no effect on profitability as proxied by ROA. This is evidenced from the partial research test which shows that the current ratio has a value of tcount < ttable, namely -0.946 < 2.110 with a significant value of 0.357 > 0.05, and the debt to assets ratio has a value of tcount < ttable which is 1.140 < 2.110 with a significant level of 0.270 > 0.05, and the simultaneous research test also showed no effect, this was seen from the value of fcount < ftable, which was 1.101 < 3.55 with a significant value of 0.355 > 0.05. For the R square value of 0.115 or equal to 11.5%. This figure means that the liquidity variable (X1) and solvency variable (X2) affect profitability (Y) only by 11.5%, and it can be concluded that the influence of the independent variable (X) on the dependent variable (Y) is very weak and in explaining the dependent variable is also very limited.